Maintaining Marine Lexicon in Coastal Language Sibolga, Pondok Batu Village, Sarudik District, Ecolinguistic Studies - Panggabean, Juli Indah (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
This research discusses the noun lexicon of the Sibolga Coastal language in the marine environment in Pondok Batu Village through an ecolinguistic perspective. This study aims to describe the lingual form of marine ecolexicons in the speech communities of the Pesisir Sibolga community. The theory used in this research is ecolinguistic theory. The data were collected using two methods, namely the observation method with the basic technique of tapping and the proficient method with the basic technique of fishing. The data used to support the research were taken by interviewing, observing and distributing questionnaires. The data of this research are noun lexicon related to marine lexicon in Pondok Batu Village. From the analysis, it can be seen that the maritime lexicon in Pondok Batu Village in the Pesisir Sibolga language is divided into four lexicon groups, namely: (1) Marine Environment Fauna Lexicon (96 lexicons); (2) Marine Environment Flora Lexicon (7 lexicons); (3) Marine Environment Activity Facilities / Infrastructure Lexicon (10 lexicons); (4) Oceanic Environment Noun Lexicon (6 lexicons).